Contemporary Zakat Literacy As A Zakat Therapy Method - Nurul Maisyal (Journal of Sufism and Psychotherapy, 2021)
The study aims to explain that contemporary zakat literacy is able to become one of the methods of zakat therapy, considering the results of the zakat literacy index conducted by the BAZNAS strategic study center related to public understanding of zakat in general are still at a moderate level and very low in advanced understanding including in understanding related to contemporary zakat. Contemporary zakat has the potential to be utilized in the benefit of the existing mustahiq zakat, considering the various kinds of contemporary zakat. The more muzakki who spend their wealth to pay zakat, the more mustahiq zakat that can be eradicated from poverty too. The study used a qualitative descriptive approach. The results of this study indicate that a person's level of understanding regarding contemporary zakat greatly influences the potential for greater zakat, so that contemporary zakat literacy can become one of the methods of zakat therapy. Contemporary zakat literacy can be a therapy for prospective muzaki to carry out zakat obligations from something that they do not know much about the existence of contemporary obligations on assets. Zakat therapy makes a person calm, feels the blessing of wealth and is able to cleanse the soul from all kinds of heart diseases. Zakat awareness is raised by carrying out zakat literacy, especially contemporary zakat literacy so that more people understand the contemporary concept of zakat and pay zakat sincerely and wholeheartedly.